Pengaruh Pola Asuh Orang Tua terhadap Perilaku Keagamaan Siswa Sekolah Dasar Negeri 43 Sungai Sapiah Kota Padang - Ramasari, Agus Dian; Sulaiman, Sulaiman (Lembaga Yasin AlSys, 2024)
This research aims to determine the influence of parenting patterns on the religious behavior of class V students at SD N 43 Sungai Sapiah whose address is Jl. Air Paku, Kel. Sapiah River, RT.02/ RW.06, Kec. Kuranji, Padang City, West Sumatra Province. The research method used is a quantitative approach research method. The population in this study were fifth grade students at SD N 43 Sungai Sapiah. The research sampling technique used the Slovin formula. Data collection was carried out using a questionnaire. The data analysis technique used is the Pearson product moment correlation formula. The research results show that the calculated t value of variable X is 4.872 and the t table value obtained is 2.303 (4.872 > 2.303) and the significance value of variables And from the F test, the calculated F value of variable So it is concluded that partially or simultaneously there is a significant influence between parental parenting patterns and the religious behavior of class V students at SD N 43 Sungai Sapiah.